Factors Affecting the Image of Nursing Profession of Student Nurses - Hingkanont, Poonsuk; Nanudorn, Anusorn (NU Journal of Nursing and Health Sciences, 2023)
The purposes of this descriptive research were to study and compare the perception of the professional image of student nurses, and factors that have an impact on the perception of the nursing profession of student nurses from the Faculty of Nursing, Rajamangala University of Technology Thanyaburi. The study sample consists of 270 student nurses, year 1-4 of the 2022 academic year, from the Faculty of Nursing Rajamangala University of Technology Thanyaburi. Stratified Random Sampling was used in this study. The research tools composed of two sections of questionnaire: 1) factors related to the perception of the image of nursing profession of student nurses, and 2) the professional image of nursing profession of the student nurses.The questionnaire was tested for reliability and validity. The reliability of total questionnaires was 0.95 (section one was 0.98 and section two was 0.93) The statistical devices used for data analysis were descriptive statistics (frequency, percentage, mean, and standard deviation), One Way ANOVA, and Stepwise Multiple regression. Findings were as follows: 1) the perceived image of nursing professional of student nurses from Year 1-4 were at high level ( = 4.70,4.72,4.65,4.73 SD= .03 ,.03,.04,.04), 2). The perceived image of nursing professional from students nurse Year 1-4 were not statistically different (F=.124 α=.94), and 3) The factors that affect the perceived image of nursing professional of students nurse Year 1-4 were reference groups, experience, and environment together were affected the perceived image of nursing profession of student nurses at the Faculty of Nursing Rajamongala University of Technology Thanyaburi at 93.7 % The result shows that the perception of the image of nursing professional of student nurses can be influenced by reference groups, experience, and environment. The institute of Nursing Education should encourage administrator, instructor, and related person who involves in the nursing program to perform a good professional nurse model for the students including promoting experience and setting environment to support image of nursing professional for student nurses continually.